Socioeconomic position, perceived weight, lifestyle risk, and multimorbidity in young adults aged 18 to 35 years: a Multi-country Study - Ashleigh Craig; Asanda Mtintsilana; Witness Mapanga; Siphiwe N. Dlamini; Shane A. Norris (BMC, 2023)
Abstract Background Multimorbidity-risk is established early in life, therefore reducing modifiable risk factors such as overweight or obesity may, in part, tackle the burden of multimorbidity in later life. Methods We made use of a cross-sectional online survey that included young adults (18-35yrs old) from three countries - Kenya, South Africa, and the United Kingdom (n = 3000). Information pertaining to socio-demographic, health, lifestyle, and perceived weight was collected. Additionally, the sum of affirmed morbidities was used to determine a morbidity score. Likewise, a lifestyle risk score was calculated based on information obtained from questions surrounding four unhealthy lifestyle behaviours, namely current smoking, alcohol consumption, physical inactivity, and overweight/obese weight status as a confirmed clinic condition. We further explored differences in socioeconomic position, and the prevalence of perceived weight, multimorbidity, and lifestyle risk factors between the three countries. We also determined the odds ratio of multimorbidity with perceived weight as a main predictor variable. We furthermore performed a generalised structural equation model to determine whether the association between socioeconomic position and multimorbidity was mediated via perceived weight and/or lifestyle risk. Results Socioeconomic position, weight perceptions, lifestyle risk, and multimorbidity varied significantly across the different economic countries. Higher morbidity (by > 11.9%) and lifestyle risk (by > 20.7%) scores were observed in those who reported an overweight weight perception when compared to those with an underweight or normal weight perception. In pooled analyses, the odds ratio in developing 2 or more morbidities increased multiple times in those who perceived themselves as overweight (all models: OR ≥ 2.241 [95% CI ≥ 1.693; ≥ 2.966] p < 0.001), showing a larger odds ratio with high significance in those who reported 3 or more morbidities (all models: OR ≥ 3.656 [95% CI ≥ 2.528; ≥ 5.286] p < 0.001). Furthermore, this study showed that an overweight weight perception partially mediated (p ≤ 0.001) the association between socioeconomic position and multimorbidity. Conclusions This study confirmed poorer health outcomes in those who perceived themselves as overweight. The findings from this study further emphasise the importance of targeted intervention strategies directed at raising weight-related awareness and potentiating risk factors, specifically in those who reside in lower economic developed countries.